Environment, development, agriculture : integrated policy through human ecology - Glaeser, Bernhard. (Routledge revivals., 2010)
This reissue, first published in 1995, focuses on philosophy and social science in human ecology, and includes case studies dealing with the problems of political implementation of development plans and schemes. Part One deals with theory, including a comprehensive introduction to the field and an overview of the conceptual modelling typical in human ecology. Part Two moves towards questions of human behaviour and action, exploring the relationship between environmental ethics and policy in terms of the justification and implementation of human interactions with nature and the environment o.